Ordinances of the Borough of Asbury Park, New Jersey, Ordinance No. 3, §1 (1878) - (:unkn) unknown (General Publisher, 1878)
no person shall discharge any cannon or other piece of artillery or small arms, guns or pistols, rockets, squibs or powder crackers, within the limits of this Borough, without the permission of the President of this Board first obtained in writing
--
Keywords: DISCHARGE